DEVELOPMENT OF TOMATO SORTING PROTOTYPE BASED ON ITS WEIGHT, COLOR, AND DIAMETER - Rahayuningtyas, Ari
Tomato is a type of horticulture plant that has many benefits and also a multipurpose commodity. Post-harvest handling of tomato, particularly sorting, has an important role in determining the quality of tomatoes. Farmers are currently sorting manually so that the results are not the same weight, color, and diameter, it also time consuming. To overcome this problem, this study implements a weight sensor and image processing for tomato sorter device, so that it can detect the weight, the color, and the diameter of tomatoes automatically.